Positive Predictive Value of Ultrasonography for Detection of Ovarian Masses Taking Magnetic Resonance Imaging as a Gold Standard - Naila Jabeen, Amjad Sattar, Marium Moula Bakhsh, Naureen Farhan, Rabeeya Qutub Uddin Siddiqui, Amber Noorani (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the efficacy of ultrasonography in the detection of ovarian masses considering MRI a Gold standard. Study design: Prospective analytical cross-sectional study Place and duration of study: Dow Institute of Radiology, Dow University of Health Sciences Karachi, Pakistan from 1st June 2018 to 30th November 2019. Methodology: One hundred and forty eight ovarian cancer patients were enrolled. Results: The mean age of the patient was 41.87±16.30 years. The majority of the patients were age ≥20 years (29.10%) and obese (33.1%). Malignant tumors were 56.1% (n=83) and 64.2% (n=95) respectively on ultrasound and magnetic resonance imaging. Ultrasound had a positive predictive value of 80%, sensitivity of 98.11%, and specificity of 86.32 % for the diagnosis of ovarian masses. Overall diagnostic accuracy of ultrasonography was 90.54%. There was an excellent agreement between the ultrasonography and magnetic resonance imaging (kappa=0.84, p-value <0.001) and area under the curve was 92.2%. Conclusion: Ultrasonography has excellent diagnostic accuracy in the detection of ovarian masses. Keywords: Ovarian mass/tumor, Ultrasonography, MRI, Positive predictive value, Benign, Malignant